Diatom volatile organic compound production is driven by diel metabolism and the cell cycle - Padaki, Vaishnavi G.; Palmer, Emily; Jiang, Yuan; Buchholz, Holger H.; Kimbrel, Jeffrey A.; Halsey, Kimberly H. (Frontiers in Microbiology, 2025)
IntroductionVolatile organic compounds (VOCs) are small, low-vapor-pressure molecules emitted from the surface ocean into the atmosphere. In the atmosphere, VOCs can change OH reactivity and condense onto particles to become cloud condensation nuclei. VOCs are produced by phytoplankton, but the conditions leading to VOC accumulation in the surface ocean are poorly understood.MethodsIn this study, VOC accumulation was measured in real time over a 12 h day−12 h night cycle in the model diatom Phaeodactylum tricornutum during exponential growth.ResultsSixty-three m/z signals were produced in higher concentrations than in cell-free controls. All VOCs, except methanol, were continuously produced over 24 h. All VOCs accumulated to higher concentrations during the day compared to the night, and 11 VOCs exhibited distinct accumulation patterns during the morning hours. Twenty-seven VOCs were associated with known metabolic pathways in P. tricornutum, with most VOCs involved in amino acid and fatty acid metabolism.DiscussionPatterns of VOC production were strongly associated with diel shifts in cell physiology and the cell cycle. Diel VOC production patterns give a fundamental understanding of the first steps in VOC accumulation in the surface ocean.